1981
DOI: 10.1055/s-2007-1019346
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a β-Receptor Agonist (Salbutamol) on Peripheral Thyroid Metabolism in Euthyroid Subjects

Abstract: IntroductionIt is now well documented that DL propranolol produces a decrease in plasma concentrations of L-triiodothyronine (T 3 ) and a rise in serum reverse T 3 (rT 3 ) in euthyroid, hyperthyroid and hypothyroid subjects on thyroxine (T 4 ) supplements (Harrower, Fyffe, Horn and Strong 1977; Lumholtz, Siersbaek-Nielsen, Faber, Kirkegaard and Frits 1978;Jung, Shetty and James 1980). DL propranolol inhibits T 4 deiodination to T 3 at peripheral sites by a reduction of the T 3 production rate, the clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…However, administration of adrenoceptor agonists also seems to interact with either thyroid hormone secretion or metabolism. In previous studies it was found that terbutaline, administered to normal-weight subjects fed on a normal diet, significantly increased the serum T3 level and the serum T3/T4 ratio [14,321, although this effect has not been confirmed by others [35]. In our study we found that both the.…”
Section: Discussioncontrasting
confidence: 74%
“…However, administration of adrenoceptor agonists also seems to interact with either thyroid hormone secretion or metabolism. In previous studies it was found that terbutaline, administered to normal-weight subjects fed on a normal diet, significantly increased the serum T3 level and the serum T3/T4 ratio [14,321, although this effect has not been confirmed by others [35]. In our study we found that both the.…”
Section: Discussioncontrasting
confidence: 74%
“…35,36 On the other hand, beta-adrenergic agonists have not been reported to cause significant changes in thyroid function tests. 37…”
Section: ■ Beta-blockers Beta-agonists and Thyroid Functionmentioning
confidence: 99%